Kinerja Karyawan Ditinjau Dari Tingkat Kesejahteraan Karyawan dan Peluang Pengembangan Karir pada PT. DANLIRIS Sukoharjo tahun 2015 - Kusumawardhani, Julian Pascalia, Dr. H. Sabar Narimo, MM., M.Pd (2015)
The purpose of this study was to determine 1) the influence of the welfare of employees on employee performance, 2) the influence of career development opportunities to employees performance, 3) the influence of the welfare of employees and pengmbangan career opportunities to employees performance. The method used is associative research approach using angket.Penelitian kuantitatif.Teknik data collection was conducted in PT. DANLIRIS Sukoharjo in June with a population 360.Sebelum instruments used, first conducted trials (try out) instrumen.Instrumen tested to employees who are on the outside of the sample population. Samples were taken based on the tables Isaac and Michael with a level of 95% which is a number of 177 respondents using simple random hypothesis testing sampling.Sebelum first tested the prerequisite analysis. The conclusion of this study were 1) the level of employee wellbeing positive effect on employee performance. It is based on multiple linear regression analysis obtained t> t table, namely 7.825> 1.984 and the significance value <0.05 is 0.000 with the relative contribution of 67.2443% and the effective contribution of 38.531%, 2) career development opportunities has positive influence on employee performance. It is based on multiple linear regression analysis obtained t> t table, namely 4.267> 1.984 and the significance value <0.05 is 0.000 with the relative contribution of 32.783% and 18.785% effective contribution, 3) the level of employee welfare and career development opportunities has positive influence on performance employees. This is evidenced by Fhitung = 116.593> Ftabel = 3.00 and a significance value <0.05 is 0.000. The result of the coefficient of determination (R2) of 0.573 obtained mean pngaruh provided by a combination of a variable quality of service and facilities on consumer satisfaction was 57.3% while the remaining 42.7% is influenced by other variables not examined. Keywords: employee welfare, career development opportunities, employee performance.